Personality Traits and Social Support as Predictors of Entrepreneurial Preference among Students in a Higher Institution in Ibadan, Oyo State - EHONDOR, G. Esohe; TAYLOR, Oladapo; UYE, E. Emmanuel (Covenant Journal of Entrepreneurship, 2024)
Graduates unemployment has remained a sticking issue among the Nigerian youths as many universities turned out thousands of graduates every year. Studies have examined several predictors of entrepreneurial preferences with varying results. Therefore, this study investigated personality traits and social support as predictors of entrepreneurial preference among students of a tertiary institution in Ibadan. The study adopted cross-sectional survey design while purposive sampling technique was used to select the Federal College of Agriculture, Moor Plantation, Ibadan. Data were collected from 206 participants using validated questionnaires. Data were analysed using t-test for independent samples and multiple regression analysis while the tested were accepted at a p < 0.05 level of significance. The result indicated that personality traits of extraversion, neuroticism, conscientiousness, agreeableness, openness to experience and social support jointly predicted entrepreneurial preference among study participants (R2 = 0.32, F (6,198) = 15.58, p < 0.05). Also, the results revealed that extraversion (β = 0.43, t =5.91, p < 0.05) and agreeableness (β = 0.17, t = 2.33, p < 0.05) independently predicted entrepreneurial preference among study participants. Finally, the result showed that social support significantly influenced entrepreneurial preferences (t (203) = 6.25, p < 0.05) among study participants. The study concluded that personality traits and social support are strong predictors of entrepreneurial preference among study participants. It is recommended that the government and various shareholders should profile students while in school and provide social support to encourage them to go into self-employment after graduation.